Hands-on robotics programming with C++ leverage raspberry pi 3 and c++ libraries to build intelligent robotics applications - Tavasalkar, Dinesh (Packt Publishing Ltd, 2019)
C/C++ is one the legacy programming language for Robotics Programming. This book will help you understand and build complexly structured robots and implement various C/C++ programming libraries in it.